Effect of partial substitution of wheat flour with date powder on biscuit quality - Sulieman, Abdel Moneim; Masaad, Mouada; Ali, Ali (Gezira Journal of Agricultural Science; Vol 9 No 2 (2011), 2011)
In this study, date powder obtained from date (Phoenix dactylifera L.) fruits was used at 5% and 10% replacement levels of wheat flour for production of biscuits. The proximate chemical composition was determined for jawa and gondella date fruit cultivars. The chemical analysis of biscuit supplemented with date powder indicated that the contents of moisture and ash ranged between 3.00 + 0.09% to 3.8 + 0.24% and 1.23 + 0.084% to 1.84 + 0.084%, respectively, while protein, oil, crude fiber and carbohydrates contents were 10.7 + 0.084% to 11.9 + 0.09%, 16.00 + 0.73% to17.7 + 0.16%, 1.00 + 0.22% to 1.9 + 0.084% and 63.46 + 0.09% to 66.5 + 0.18%, respectively. On the other hand, the content of sodium and potassium were within the range of 3.00 to 3.44 and 20 to 32.54 mg/100 g, respectively. The content of iron ranged between 2.00 to 4.70 mg/100 g. Microbial analysis revealed the presence of 5x 10 5 to 1.8 x 10 4 c.f.u/g total viable count and all biscuit samples were free from moulds and yeasts. The sensory evaluation of the different biscuit samples revealed that there were no significant differences between biscuit made from the different blends of wheat flour and date powder. However, panelists gave higher scores to the 5% date powder ( Jawa ) than the biscuit made from other blends. في هذه الدراسة تم استخدام بدرة التمر المتحصل عليها من ثمار التمر في إنتاج البسكويت بنسبة %5 و10% من دقيق القمح لانتاج البسكويت. تم اجراء التحليل الكيميائي التقريبي لعينات ثمار التمر جاوا وقنديله. أوضح التحليل الكيميائي للبسكويت المضاف إليه بدرة التمر الى أن محتوي الرطوبة والرماد كان بين 3.00 + 0.09 الى 3.8 + 0.24 و 1.2 + 0.084 إلى 1.84 + 0.084 على التوالي بينما محتوى البروتين والدهن والألياف والكاربوهيدريتات تقع بين  10.7 + 0.08 الى 11.9 + 0.09 ، 16.00 + 0.73 الى 17.7 + 0.16 ، 1.00 + 0.22 الى 1.9 + 0.084 و 63.46 + 0.09 الى 66.5 + 0.18 على التوالي. وقع محتوي الصوديوم والبوتاسيوم (ملجم/100جم) فى المدى 3.00 الى 3.44 و 20 الى 32.54 على التوالي. أظهر التحليل الميكروبي وجود 5 × 5 10 الى 1.8 × 4 10  (مستعمرة/الجرام)  للعدد الكلي للبكتريا وكانت جميع عينات البسكويت خالية من خلايا الأعفان  والخمائر. أجرى تقييم حسي بواسطة محكمين لكل أنواع البسكويت ولقد أعطى المحكمون درجة قبول أعلى نسبياً للبسكويت المصنّع بإضافة 5% من بدرة  تمر الجاوا.